STUDY ON INTEGRATED NUTRIENT MANAGEMENT IN GROUNDNUT AT FARMERS FIELD - SINGH, MOOL CHAND (Annals of Agricultural Research, 2014)
An on farm trail was conducted in the deep black soil at farmers field in Hulkoti taluk in the Gadag district of Karnataka revealed that higher dose of fertilizer (150% of recommended dose) application had resulted in increased yield (22.8 q/ha) compared to the farmers practice of manure and fertilizer application (18.0 q/ha). The pod yield was further enhanced to 24.2 q/ha due to addition of 10 kg /ha each of ZnSO4 and FeSO4 along with recommended dose of fertilizers. However, pod yield that was obtained by micro nutrient application (10 kg each of ZnSO4 and FeSO4) along with fertilizer was at par with that of 150 per cent recommended dose of fertilizers. But, net return and B:C ratio were higher for the treatment that received 100 per cent recommended dose of fertilizers along with 10 kg each of ZnSO4 and FeSO4. Therefore, recommended dose of fertilizer along with micronutrients is essential to obtain economic yields in the black soil of Gadag district in Karnataka instead of applying only higher doses of fertilizers. The manure applied plots did not record higher net return as well as B:C ratio. N and P content in groundnut tissue increased with the 150 percent recommended dose of fertilizer application. Potassium content of the tissue remained unaffected due to fertilizer, manure and micro-nutrient application.